Knowledge, Acceptance, and Satisfaction about Dental Implant among Patients of Patan District of Gujarat - Rukhshana N. Shaikh; Chirag J. Chauhan; Nikunj Prajapati; Komil Tintodana; Ghanshyam Patel; Abhay Machchar (Wolters Kluwer Medknow Publications, 2024)
Context: Patan is a district of North Gujarat having a mainly rural population. Here, patients are having lack of knowledge with regard to the replacement of teeth especially by dental implant option. Aim: To know about the awareness and knowledge of dental implant as well as its acceptance and satisfaction rate among patients as a replacement option for missing teeth in patients of Patan district of Gujarat state. Settings and Design: A self-explanatory questionnaire-based study. Methods and Material: About 707 out of 800 patients were included in the present study. Results: Only 28.6% of participants knew about dental implant treatment for the replacement of missing teeth. The younger and more educated participants showed more awareness and knowledge with slight differences within gender. Patients showed just 24.7% acceptance. Around 76.3% of participants noted satisfaction by their known acquaintances about dental implant treatment. Conclusions: This study demarcates a lack of awareness and knowledge of dental implants in the patients of the Patan district. The government has to arrange the awareness program repeatedly for patients about restoration of the missing teeth by using different means and avail dental implant treatment in government-based hospitals.